From 'it makes me feel free' to 'they won't let me play': the body and physical activity-related perceptions and experiences of children with congenital heart disease and their parents. Issue 2 (4th March 2021) - Bennett, E. V.; Voss, C.; Faulkner, G.; Harris, K. C.
ABSTRACT: The purpose of this study was to examine the body and physical activity perceptions and experiences of children with congenital heart disease (CHD) and of their parents to advance understanding of how they make sense of and navigate the complexities of the children's physical activity participation in the context of their everyday lives. Guided by narrative constructionism, we conducted semi-structured interviews with 16 children aged 9 to 12 and their parents (32 interviews total) and examined the content of and core patterns within their body and physical activity-related stories. Children derived pleasure, social connection, physical literacy, and health and well-being from activity engagement. Children and parents experienced complex emotional webs of pride, embarrassment, shame, envy, and fear/anxiety in relation to the body and physical activity, however, attempted to manage these emotions to foster sustained activity involvement. While children engaged in safe yet pleasurable activities by self-regulating, parents attempted to hide their worries surrounding their children's self-regulatory abilities. Cultural narratives of risk, healthism, and disability were drawn upon by participants when structuring their stories, thereby shaping the body and activity-related cognitions, emotions, and behaviours they experienced. This study highlights the utility of narrative inquiry to examine the complexities of children with CHD's activity participation, including the role of the sociocultural milieu in shaping body and physical activity-related psychological states. The findings can guide activity leaders, parents, and health-care practitioners in how to foster inclusive physical activity programming to optimise the health and well-being of children with CHD.